Recovery of Motor Imagery Ability in Stroke Patients. (3rd March 2011) - de Vries, Sjoerd; Tepper, Marga; Otten, Bert; Mulder, Theo
Abstract : Objective . To investigate whether motor imagery ability recovers in stroke patients and to see what the relationship is between different types of imagery and motor functioning after stroke. Methods . 12 unilateral stroke patients were measured at 3 and 6 weeks poststroke on 3 mental imagery tasks. Arm-hand function was evaluated using the Utrecht Arm-Hand task and the Brunnström Fugl-Meyer Scale. Age-matched healthy individuals (N = 10 ) were included as controls. Results . Implicit motor imagery ability and visual motor imagery ability improved significantly at 6 weeks compared to 3 weeks poststroke. Conclusion . Our study shows that motor imagery can recover in the first weeks after stroke. This indicates that a group of patients who might not be initially selected for mental practice can, still later in the rehabilitation process, participate in mental practice programs. Moreover, our study shows that mental imagery modalities can be differently affected in individual patients and over time.